A "turn-on" fluorescent probe for the detection of permanganate in aqueous media. Issue 10 (15th January 2019) - Shi, Genggongwo; Shahid, Mushtaq Ahmed; Yousuf, Muhammad; Mahmood, Farzana; Rasheed, Lubna; Bielawski, Christopher W.; Kim, Kwang S.
Abstract : A novel carbazole-based probe exhibit fluorescence upon introduction to permanganate in aqueous media. Abstract : A novel carbazole-based probe was synthesized and found to exhibit fluorescence upon introduction to potassium permanganate in aqueous media. Guided by a series of experimental studies and DFT calculations, the underlying mechanism is proposed to proceed through a series of tandem proton and electron transfer processes.